An Anomalous Formation, Distribution, and Branches of Brachial Plexus with Its Embryological and Clinical Correlation: A Case Report - Singh , Pooja; Sinha , Manisha B. (Research Developments in Medicine and Medical Science Vol. 10, 2023)
The purpose of this study is to unfold the complexity of brachial plexus. These variations might not affect the functioning of upper limb of that individual but knowledge of these variations will be important to evaluate unexplained sensory or motor loss after trauma or during surgical interventions of upper limb. Brachial plexus is complex network of nerves that are solely innervated to upper limbs. Information about its variations is important for anatomists, anesthesiologists, clinicians especially for surgeons during surgical explorations of the axilla and the arm region. It represents a rare pathology in the general population, with rates of incidence and prevalence difficult to quantify exactly. Most of these injuries determine relevant motor and sensory impairments of the upper limb, with disability and functional limitations. During routine dissection classes of first year MBBS students, we reported formation of only two trunks i.e. upper trunk (C5 and C6) and lower trunk (C7, C8 and T1) while middle trunk was completely absent in 70 year old male preserved cadaver. Other anomalies of the same plexus were also discovered, such as the fact that all three cords and their branches, regardless of their component parts, lie lateral to the axillary artery. Both musculocutaneous nerve and various lateral cord branches supplied the coracobrachialis. The superior thoracic artery was encircled by a loop created by the joining of the medial and lateral pectoral nerves. The median nerve's lateral and medial roots were able to communicate with one another. It also helps the clinicians for post traumatic evaluation and to explore peripheral nerve restoration of upper limb.